An experimental investigation of the Akamai adaptive video streaming - Luca De Cicco; Saverio Mascolo (Proceedings of the 6th International Conference on HCI in Work and Learning, Life and Leisure: Workgroup Human-Computer Interaction and Usability Engineering, 2010)
Akamai offers the largest Content Delivery Network (CDN) service in the world. Building upon its CDN, it recently started to offer High Definition (HD) video distribution using HTTP-based adaptive video streaming. In this paper we experimentally investigate the performance of this new Akamai service aiming at measuring how fast the video quality tracks the Internet available bandwidth and to what extent the service is able to ensure continuous video distribution in the presence of abrupt changes of available bandwidth. Moreover, we provide details on the client-server protocol employed by Akamai to implement the quality adaptation algorithm. Main results are: 1) any video is encoded at five different bit rates and each level is stored at the server; 2) the video client computes the available bandwidth and sends a feedback signal to the server that selects the video at the bitrate that matches the available bandwidth; 3) the video bitrate matches the available bandwidth in roughly 150 seconds; 4) a feedback control law is employed to ensure that the player buffer length tracks a desired buffer length; 5) when an abrupt variation of the available bandwidth occurs, the suitable video level is selected after roughly 14 seconds and the video reproduction is affected by short interruptions.